Análisis del principio de favorabilidad e igualdad en la firmeza de las declaraciones tributarias nacionales - Torres Sanchez, Olga Stefany (Universidad Antonio Nariño, 2021)
As Colombia is a social State governed by law, as established in its Political Constitution, its regulations must guarantee the rights of citizens in relation to constitutional precepts, however we find that some laws stimulate inequality between the State and the possibility of defense of fellow citizens, it is so, as in the ET After the reform introduced by law 1819 of 2016, the Tax Administration was granted a longer term to be able to audit the tax returns, this, as a consequence of the increase in the term of firmness of said returns, which clearly implies an inequality of procedural weapons, since the taxpayer, person in charge or declarant in the face of the possibility of correcting their declarations has a term not exceeding 2 years, which would leave a dead time of 1 year, in which the prosecuted person can still perform it cannot do voluntary corrections to these declarations, but nevertheless the Administration during this term can make a display of its supervisory and sanctioning power against the declarants, the previous thing to our judgment goes against the article 29 of the Political Constitution, as for it conflicts with the principles of favorability, equity and due process; It is understandable that a reform of this category has as arguments the fight against Tax evasion, the persecution of paper companies and money laundering, prevailing for the time, wanting the State to have a longer period of time to control said operations, however this cannot go against the fundamental principles of Magna Carta.